2018
DOI: 10.3389/fneur.2018.00348
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Footstep Sounds as Rhythmic Auditory Stimulation for Gait Rehabilitation in Parkinson’s Disease: A Randomized Controlled Trial

Abstract: BackgroundThe use of rhythmic auditory stimulation (RAS) has been proven useful in the management of gait disturbances associated with Parkinson’s disease (PD). Typically, the RAS consists of metronome or music-based sounds (artificial RAS), while ecological footstep sounds (ecological RAS) have never been used for rehabilitation programs.ObjectiveThe aim of this study was to compare the effects of a rehabilitation program integrated either with ecological or with artificial RAS.MethodsAn observer-blind, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 61 publications
0
74
0
Order By: Relevance
“…This study employed the commonly used metronome cue for RAS delivery, though recent work has demonstrated the benefit of RAS that uses footstep sounds instead ( 46 , 47 ). The use of footstep sounds is equally effective in improving motor recovery scores and more effective than metronome cueing for improving spatiotemporal gait parameters such as speed, cadence, and step length for individuals with Parkinson's disease ( 48 ). Given its relation to the motor task being performed, it is possible the use of footstep sounds as RAS may facilitate the rhythmic perception of individuals with weak ability who attempt to match their gait to the cue.…”
Section: Discussionmentioning
confidence: 99%
“…This study employed the commonly used metronome cue for RAS delivery, though recent work has demonstrated the benefit of RAS that uses footstep sounds instead ( 46 , 47 ). The use of footstep sounds is equally effective in improving motor recovery scores and more effective than metronome cueing for improving spatiotemporal gait parameters such as speed, cadence, and step length for individuals with Parkinson's disease ( 48 ). Given its relation to the motor task being performed, it is possible the use of footstep sounds as RAS may facilitate the rhythmic perception of individuals with weak ability who attempt to match their gait to the cue.…”
Section: Discussionmentioning
confidence: 99%
“…Open-loop studies have most widely utilized auditory or visual forms of cues to improve gait in people with PD. While auditory cues have most often been delivered as rhythmic auditory stimulation (RAS) or metronome beats in accordance to the user's preferred gait speed or cadence [36,[42][43][44][45][46], other types of cues such as highly rhythmic music or verbal instructions have also been investigated in some of the studies [43,44,47]. Most forms of visual cueing present lines or markers on the floor as targets for foot placement.…”
Section: Cueing For Rehabilitation In Pdmentioning
confidence: 99%
“…Studies of open-loop cueing used as a therapeutic modality have demonstrated short-term and long-term gait improvements [41][42][43]48,[58][59][60][61]. Short-term studies investigated immediate effects with and without different cue interventions [62][63][64].…”
Section: Cueing For Rehabilitation In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…The MNS involvement has been improved by the object-oriented visual stimulus (Li et al, 2015 ). The MNS has been proved as a crucial role during the ecological stimuli (Murgia et al, 2015 , 2016 , 2018 ; Sors et al, 2015 ; Pizzera et al, 2017 ), and furthermore, the ecological visual and auditory stimuli can effectively affect complex movements (Kennel et al, 2014 ; Camponogara et al, 2016 ; Murgia et al, 2017 ). The rhythmic auditory stimulation is also indicated to facilitate gait rehabilitation (Thaut et al, 1993 , 1996 ; Pau et al, 2016 ; Dalla Bella et al, 2017 ; Bailey et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%